Is Perioperative Dexmedetomidine Associated With a Reduced Risk of Perioperative Neurocognitive Disorders Following Cardiac Surgery? A Systematic Review and Meta-Analysis With Trial Sequential Analysis of Randomized Controlled Trials - Xiong, Xinglong; Chen, Dongxu; Shi, Jing (Frontiers in Medicine, 2021)
Background: To assess the effect of dexmedetomidine on the reducing risk of perioperative neurocognitive disorders (PNDs) following cardiac surgery. Methods: A systematic review and meta-analysis with trial sequential analysis (TSA) of randomized controlled trials were performed. PubMed, Embase, Cochrane Library, and CNKI databases (to August 16, 2020) were searched for relevant articles to analyze the incidence of PND for intraoperative or postoperative dexmedetomidine administration after cardiac surgery. PND included postoperative cognitive dysfunction (POCD) and postoperative delirium (POD). Results: A total of 24 studies with 3,610 patients were included. Compared with the control group, the incidence of POD in the dexmedetomidine group was significantly lower (odds ratio [OR]: 0.59, 95% CI: 0.43–0.82, P = 0.001), with firm evidence from TSA. Subgroup analyses confirmed that dexmedetomidine reduced the incidence of POD with firm evidence following coronary artery bypass grafting surgery (OR: 0.45, 95% CI: 0.26–0.79, P = 0.005), and intervention during the postoperative period (OR: 0.48, 95% CI: 0.34–0.67, P < 0.001). Furthermore, the incidence of POD in the dexmedetomidine group was also decreased in mixed cardiac surgery (OR: 0.68, 95% CI: 0.47–0.98, P = 0.039). Irrespective of whether “Confusion Assessment Method/Confusion Assessment Method for intensive care unit” or “other tools” were used as diagnostic tools, the results showed a decreased risk of POD in the dexmedetomidine group. There was no significant difference in the incidence of POCD (OR: 0.47, 95% CI: 0.22–1.03, P = 0.060) between the two groups, but this result lacked firm evidence from TSA. Conclusion: The administration of dexmedetomidine during the perioperative period reduced the incidence of POD in patients after cardiac surgery, but there was no significant benefit in the incidence of POCD. The effect of dexmedetomidine on the incidence of POD or POCD following different types of surgery and the optimal dose and timing of dexmedetomidine warrant further investigation. Trial registration: PROSPERO registration number: CRD42020203980. Registered on September 13, 2020.